Analisis Relevansi Nilai Informasi Akuntansi Sebelum dan Setelah Penerapan PSAK 72 di Indonesia - Widaningsih, Mimin; Mediawati, Elis; Revita, Ira; Hazim, Raihan; Nuriyah, S. Rizka (Juara: Jurnal Riset Akuntansi, 2024)
PSAK 72 is still considered a new PSAK, namely it will become effective in 2020, so research still needs to be carried out regarding the effect of implementing PSAK 72 in terms of the level of value relevance of the accounting information.  This research is a quantitative research with descriptive and verification methods which aims to empirically test the differences in the relevance of the value of accounting information as measured by the Ohlson model for the period before and after the implementation of PSAK 72 concerning Income from Contracts with Customers in Property and Real Estate Sector companies.  The research results show that before the implementation of PSAK 72 variables that had relevance value for accounting information were only Book Value Per Share, whereas after the implementation of PSAK 72 variables that had relevance value for accounting information were Earning Per Share and Book Value Per Share.  Then, before and after the implementation of PSAK 72, Earning Per Share and Book Value Per Share together have the relevance of the value of accounting information.  Furthermore, there is an increase in the relevance of accounting information after the implementation of PSAK 72 in Property and Real Estate Sector companies.